FRETing about the details: Case studies in the use of a genetically encoded fluorescent amino acid for distance‐dependent energy transfer. (17th April 2023) - Cory, Michael B.; Jones, Chloe M.; Shaffer, Kyle D.; Venkatesh, Yarra; Giannakoulias, Sam; Perez, Ryann M.; Lougee, Marshall G.; Hummingbird, Eshe; Pagar, Vinayak V.; Hurley, Christina M.; Li, Allen; Mach, Robert H.; et al.
Abstract: Förster resonance energy transfer (FRET) is a valuable method for monitoring protein conformation and biomolecular interactions. Intrinsically fluorescent amino acids that can be genetically encoded, such as acridonylalanine (Acd), are particularly useful for FRET studies. However, quantitative interpretation of FRET data to derive distance information requires careful use of controls and consideration of photophysical effects. Here we present two case studies illustrating how Acd can be used in FRET experiments to study small molecule induced conformational changes and multicomponent biomolecular complexes.